Peace In Every Relationship: Building an Interdisciplinary, Holistic Domestic Violence Program on College Campuses (In Factis Pax: Journal of Peace Education and Social Justice, 2013)
Despite recognition that college-aged students are particularly at-risk for experiencing abusive relationships (Fisher, Cullen & Turner, 2009; Leonard, Quigley & Collins, 2002; Sellers & Bromley, 1996; Schwartz & DeKeseredy, 1997; Strauss, 2008), the creation and implementation of impactful campus-based educational programming remains a challenge. Some colleges and universities are teaching domestic violence by adding specific courses or even whole programs on the topic, but more  frequently the academic coverage of this topic comes from units or event one-time lectures within specific courses. Those programs that address the issue more extensively tend to be directed at the graduate level (see for example University of Central Florida, University of Colorado at Denver, etc.). Due to the siloed nature of higher education, rarely are curricular approaches to domestic violence education interdisciplinary in nature (Astin & Astin, 2000; Harkavy, 2006). Yet it is clear that a true understanding of the issues and dynamics related to domestic violence necessitates a multi-disciplinary approach (Allen-Meares, 1998; Colarossi & Forgey, 2006; Hall & Weaver, 2001; Retkin, Stein & Draimin, 1997; Weinstein, 1999). Further, it is hard to believe that ad-hoc approaches reach the masses of students who might at some point in their lives experience or be impacted by abuse, nor those who wish to get involved (Fisher, Cullen & Turner, 2009).